Painless performance conversations : a practical approach to critical day-to-day workplace discussions - Green, Marnie E. (Listen Alaska., 2013)
Actionable communication and management strategies for tackling difficult workplace discussions Delivering the uncomfortable news that an employee is not stacking up can be stressful, and managers often have difficulties finding the right words to get their message across. Painless Performance Conversations presents actionable and practical communication and management strategies for any manager looking to effectively influence employee performance. Learn how to focus these conversations for maximum impact on performance, crystallize expectations for what success looks like, and engage employees in solution-finding. Presenting four key mindsets and an easy to use conversation model, this book offers the tangible solutions managers need to tackle critical workplace discussions with poise and professionalism, as well as the tools needed to stay focused in otherwise difficult conversations.-Eliminates the pain and fear that leads to procrastination of tough workplace conversations.-Reduces the harmful impacts of judgment in performance conversation -Helps managers create a culture of ownership and accountability -Author Marnie E. Green is a featured blogger for Jobing.com and shares her popular and practical management perspectives in keynotes, webinars, and workshops with thousands of leaders in organizations worldwide Painless Performance Conversations will help you to lead performance-related conversations with confidence and create a culture of workplace accountability.